2004
DOI: 10.1071/ar03106
|View full text |Cite
|
Sign up to set email alerts
|

Effect of liquid to feed ratio, steeping time, and enzyme supplementation on the performance of weaner pigs

Abstract: 2Two experiments were conducted to examine the effect of liquid to feed ratio, steeping time 3 and enzyme supplementation on performance of weaner pigs. In Expt. 1, 40 male weaner 4 pigs (weaned at 27 days of age) were randomly allocated to four treatments, including a dry 5 fed control and three liquid diets of differing liquid: feed ratios (2:1, 3:1 and 4:1). Pigs were 6 fed individually. Body weight was measured weekly and feed intake measured daily. The 7 results confirmed the advantage of liquid feeding b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 10 publications
1
13
0
2
Order By: Relevance
“…One major challenge apart from the presence of theobromine in cocoa by-products is the high crude fibre content or non-starch polysaccharides (NSP). Choct (2004) indicated that NSP are poorly digested by monogastric animals such as pigs because they do not produce enzymes that are capable of digesting these fibre components. According to Bedford (2000), exogenous enzymes can be used to address the problems of some anti-nutritional factors and high fibre levels that limit feed value, thereby leading to a more economic and efficient utilization of AIBP.…”
Section: Introductionmentioning
confidence: 99%
“…One major challenge apart from the presence of theobromine in cocoa by-products is the high crude fibre content or non-starch polysaccharides (NSP). Choct (2004) indicated that NSP are poorly digested by monogastric animals such as pigs because they do not produce enzymes that are capable of digesting these fibre components. According to Bedford (2000), exogenous enzymes can be used to address the problems of some anti-nutritional factors and high fibre levels that limit feed value, thereby leading to a more economic and efficient utilization of AIBP.…”
Section: Introductionmentioning
confidence: 99%
“…More studies in actual farm conditions are needed. Performance might be improved by the addition of exogenous enzymes such as xylanase or phytase, as reported by Choct et al. (2004b).…”
Section: Flf On Pig Performance and Conditions In The Git (Table 2)mentioning
confidence: 85%
“…A water-to-feed ratio of 3:1 or 3.5:1 improves growth and feed efficiency (Barber et al, 1991); a ratio of 4:1 might be necessary if salt rich feed are fed, e.g. whey (Mordenti and Scipioni, 1983), whereas at higher ratios ( 44:1) dry matter intake and ADG are depressed (Choct et al, 2004).…”
Section: Introductionmentioning
confidence: 99%